Deconstructing the orange: the evolution of an agricultural milieu in Southern Greece. (12th May 2004) - Lemon, Mark; Jeffrey, Paul; Seaton, Roger
Knowledge relating to the coevolution of communities and the technological, economic and natural systems that sustain them comes from a variety of sources. However, interdisciplinary, or more specifically integrated, analyses that formally consider issue-driven and policy-relevant output are now required. This paper will draw upon a case study of crop change, in particular the rapid introduction of oranges, in the Argolid Valley in Greece, and will argue that crops and other agricultural artefacts are elements of complex processes that generate social structures that are more, or less, acceptable to different social groupings. We particularly focus on an illustration of the nature of coevolutionary linkages, and highlight the fluidity of stakeholder decision and opportunity spaces and their relationship to community flexibility and adaptivity. Finally, it will be argued that policies that attempt to affect crop choice have failed to consider the range of networks into which the crop will merge.